Recent publication trends on throttle body design - Abdul Kadir, Faizul Akmar; Tahiruddin, Mohd Faqrul Radzi; Shamsudin, Shamsul Anuar; Ahmad, Fauzi; Jamaluddin, Hishammudin; Mohamad, Taib Iskandar (Universiti Malaysia Perlis, 2022)
Throttle body (TB) role in regulating air for internal combustion engine (ICE) is crucial and proven beneficiary for ICE performance. Researchers have shown interest in the study of TB which is reflected by the numbers of publication on TB. Between 2011 and 2021, seven review articles with keyword “throttle body” were published in Science Direct investigating on alternative fuel, enhancement on fuel injection technology and control system. Despite the reviews highlighted above, there remains a paucity of review on TB design. Therefore, this study gathered literatures from year 2011 to 2021, focusing on Scopus and Science Direct databases to investigate and analyse numbers of publications relating to TB design. Out of 186 publications found, only 49 articles were chosen after the inclusion and exclusion process. The findings highlighted six themes or patterns in research of TB design which are categorize as airflow study, control system design, design process study, manufacturing / production, new approach TB, and performance study. The results will benefit TB designers and provide guidelines towards a better contribution to the body of knowledge for future studies.